2019
DOI: 10.1101/667667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PRC1 catalytic activity is central to Polycomb system function

Abstract: The Polycomb repressive system is an essential chromatin-based regulator of gene expression. Despite being extensively studied, how its target genes are selected and whether its histone modifying activities are required for transcriptional repression remains controversial. Here, we directly test the requirement for PRC1 catalytic activity in Polycomb system function. We demonstrate that a mutation widely used to disrupt PRC1 catalysis is hypomorphic, complicating the interpretation of previous studies. To over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(101 citation statements)
references
References 100 publications
(120 reference statements)
11
90
0
Order By: Relevance
“…Thus, through "writing" and "reading" of histone modifications, PRC1 and PRC2 engage in a feedback mechanism that promotes the formation of a repressive chromatin domain. This model is supported by recent evidence demonstrating that PRC2 recruitment is severely reduced upon complete catalytic inactivation of PRC1 (27,28). However, there is also mounting evidence for sequence-specific binding of PRC2 subunits (29)(30)(31).…”
Section: Introductionmentioning
confidence: 69%
“…Thus, through "writing" and "reading" of histone modifications, PRC1 and PRC2 engage in a feedback mechanism that promotes the formation of a repressive chromatin domain. This model is supported by recent evidence demonstrating that PRC2 recruitment is severely reduced upon complete catalytic inactivation of PRC1 (27,28). However, there is also mounting evidence for sequence-specific binding of PRC2 subunits (29)(30)(31).…”
Section: Introductionmentioning
confidence: 69%
“…Studies have also shown that the long-range interactions are lost in Ring1b –/– mESCs ( Eskeland et al, 2010 ; Schoenfelder et al, 2015 ). As RING1B is the assemblage of PRC1 ( Blackledge et al, 2020 ; Fursova et al, 2019 ; Leeb and Wutz, 2007 ), removal of RING1B disrupts the complex formation of CBX2-PRC1 and CBX7-PRC1. Thus, CBX7 on its own cannot bring the distal regions or promoters into the CBX2 condensates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that RING1B and BMI1 are the core components of PRC1 complex (Chittock et al, 2017) and BMI1 is known to play a role in cell proliferation and cell cycle, Bmi1 knockouts in mice leads to p16Ink4a upregulation and reduced the rate of proliferation in NSCs. The decreased self‐renewing capacity of Bmi1 in NSCs led to depletion of postnatal cell types; Bmi1 was found to be not needed for proliferation of neuronal and glial cell types from the forebrain (Molofsky et al, 2003; Blackledge et al, 2020). Our results also suggest that BMI1 could be actively involved during differentiation other than its known role in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We also show that BMI1 and RING1B are not expressed in same stoichiometric levels during differentiation; this could be due to variants of PRC1 complex some of which do not have BMI1, but still the PRC1 complex retains the E3 ligase activity. Also it has been recently been shown that BMI1 may not be always associated with RING1B in the PRC1 complexes, as there are variant PRC1 (vPRC1) complexes that do not have BMI1 subunit (Blackledge et al, 2020; Cohen et al, 2019; Fursova et al, 2019). We observed that PRT4165 though is catalytic activity inhibitor of RING1B, yet is caused reduction at the transcript and protein level.…”
Section: Discussionmentioning
confidence: 99%